Linear and non‑linear methods for the prediction of mandible morphology - Terblanche, Jacques (Stelenbosch : Stellenbosch University, 2025)
Terblanche, J. 2025. Linear and non‑linear methods for the prediction of mandible morphology. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/72000e8b-9b05-40d8-91c1-361327b19916